Fractionated Polysaccharide Extracts From Codium Geppiorum O.C. Schmidt, 1923: Ftir And Bioactivity Evaluation - Diaz, John Benedict B.; Maria Elma Q. Won; Felmer Latayada; Magdugo, Rexie P. (Jurusan Biologi Universitas Negeri Makassar, 2024)
This study investigates the Codium species from the class Chlorophyta, known for their bioactive polysaccharides. Hence, the two isolated polysaccharide extracts: crude polysaccharides (CPs) and acid polysaccharides (APs), with yields of 20.41% and 19.50%, respectively. Fourier-Transform Infrared (FTIR) analysis confirmed the presence of characteristic sulfated polysaccharides at 1220cm-1 -565cm-1 in APs and 880cm-1 in CPs. Antimicrobial activity was observed only in the APs, which effectively inhibited Micrococcus luteus (22±2 mm at 100 mg/mL), Pseudomonas aeruginosa (16.67±1.15 mm at 100 mg/mL), and showed trace activity against Saccharomyces cerevisiae (+=trace). The APs demonstrated significant antimicrobial effects against Gram-positive bacteria, indicating their potential for pharmaceutical and natural product applications. This work provides a foundational step toward generating innovative, seaweed antibacterial drugs, addressing the essential need for updated remedies in the peak of increasing antibiotic-resistant microorganisms.